Agronomy Tutorial Education Program and the Training and Dissemination of Knowledge during the Covid-19 Pandemic (Research, Society and Development, 2022)
The Covid-19 worldwide pandemic resulted in changes in the way knowledge was disseminated, this pattern also extended to the activities of UFGD's PET Agronomy. Given the above, the aim of this article was to report the transition and adaptation of in-person technical training and information dissemination activities to the remote format during the Covid-19 global pandemic. Soon, the VIMD - Intelligent Life at Midday and the workshops, conceived and organized by the PET-Agronomy group of the Federal University of Grande Dourados – UFGD, were reported. The activities presented in this article are related to the period from March 2020 to December 2020. This approach emphasized the organization, execution and subsequent balance of actions, as well as the adaptation of the presence for the remote period. Nine actions were carried out within VIMD, 2 in-person and 7 remote. In the transition from in-person to remote, there was initially an increase in diversity and in the number of participants, however over time there was a decrease in the number of participants resulting in changes in the format of the platforms used. These modifications resulted in the establishment of a new format for the short courses, in this format 5 actions were carried out, this form of dissemination culminated in greater homogeneity and constancy of the public, as it resulted in rapid training in a short period of time. The actions in a remote period demonstrated the need for quick adaptation, and a greater demand from the public in relation to the format.